Prescription pattern of metformin for various indications: a prospective study - Vaseem, Ayesha; Ali, Mazher; Afshan, Khuteja (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Metformin, a biguanide is the most preferred choice of drug in the treatment of type 2 diabetes mellitus. It has many advantages - it does not cause hypoglycaemia and weight gain, prevents insulin resistance besides being cheap and relatively safe. It has other pleiotropic benefits beyond its glucose-lowering effect with preclinical evidence for many indications. This prospective observational study was conducted to assess the prescribing pattern of metformin for various indications by physicians. Methods: Prescriptions containing metformin were collected from the inpatient and Outpatient Departments of different specialities. The data collected were analysed and grouped on the bases of age, gender, disease condition and analysed for significance. Results: A total of 218 patients were included in this study. All the prescriptions containing metformin were collected and analysed. Metformin was most extensively prescribed for Type 2 diabetes (51.83%) followed by Polycystic ovarian disease (PCOD) (26.14) and least number of prescriptions were collected for prediabetes (1.37%). Most common age group receiving metformin was 31-40 years (35.77%). Conclusions: Metformin is the oldest and most widely prescribed as a first choice antihyperglycemic drug for treatment of type 2 diabetes mellitus. There are many experimental and clinical studies which have shown an array of potential benefits of metformin other than in the treatment of diabetes. But its clinical application is limited despite convincing basic evidence. The possible reasons could be absence of recommendations in the guidelines and insufficient evidence for use.